THE RESONANCE OF FEMALE CONSCIOUSNESS AND STRATEGIC COMMUNICATION: A CRITICAL ANALYSIS OF FEMALE ARCHETYPES IN KUVEMPU’S SRI RAMAYANA DARSHANAM FROM AN INDIAN KNOWLEDGE SYSTEMS PERSPECTIVE - Dr. Shashikala.U (IJRDO - Journal of Social Science and Humanities Research, 2026)
The story of Ramayana has been constantly evolving with the retelling and philosophical interpretation that mirrors the intellectual and socio-cultural consciousness of their respective times. One such interpretation is the Sri Ramayana Darshanam by Rashtrakavi Kuvempu which stands apart from the rest in contemporary Indian literature for the way in which it breaks away from the traditional form of an epic tale to present the Ramayana as a philosophy of universal consciousness. While previous versions have tended to focus on dharma via the adventures of Rama, Kuvempu reinterprets the epic in terms of the evolution of consciousness (Pūrṇa Dṛṣṭi), which brings female characters as integral figures in transforming society morally, psychologically, and spiritually. This paper attempts to analyze the representation of female archetypes in Sri Ramayana Darshanam by combining the frameworks of Indian Knowledge Systems (IKS), Communication Studies, Feminist Literary Theory, and Leadership. The research explores the ways in which female characters like Sita, Urmila, Kaikeyi, Manthara, Mandodari, Trijata, Anale, and Shabari represent different kinds of Strī Prajñe (female consciousness) through ethical reasoning, strategic communication, emotional intelligence, diplomacy, organizational support, and transformative leadership. Through the qualitative method of textual hermeneutics and literary comparison, this paper proves that Kuvempu’s interpretation of feminine agency is no longer about mere resilience, but conscious participation in the evolutionary process of the cosmos itself. The women are agents of communication where their communication acts, silence, persuasion, empathy, and morality play very significant roles in the development of the epic. The women’s communication process foretells a few modern ideas like emotional intelligence, organizational communication, conflict resolution, ethical leadership, stakeholder management, mentoring, organizational support, and inter-cultural communication. The present paper goes on to prove that the philosophy behind Sri Ramayana Darśanam has very strong similarities with the ideas of Indian Knowledge Systems, such as Śakti, Dharma, Samatva, Loka-saṅgraha, and Pūrṇa Dṛṣṭi. Through the interpretation of these women as evolving agents of consciousness and not just secondary mythological characters, Kuvempu creates a timeless model for understanding the idea of leadership, gender equality, communication ethics, and social harmony.